Glacier inventory and recent variations of Santa Ines Icefield, Southern Patagonia - Gurdiel, Isaac; Rada Giacaman, Camilo Andres; Malz, Philipp; Braun, Matthias; Casassa, Gino (My University, 2022)
The study of glaciers in remote regions improves our understanding of global glacier change. With an area of 149.31 +/- 1.84 km(2), the Santa Ines Icefield constitutes one of the largest and least studied and explored glaciated areas of Southern Patagonia. We study the extent and glacier variations of the Santa Ines Icefield over the last 75 years, and we generate the most detailed glacier inventory to date of its 24 constituting glaciers. We estimate surface elevation changes between 2000 and 2014 using Shuttle Radar Topography Mission (SRTM) and TanDEM-X digital elevation models. Our results show a generalized trend of retreat, with a glacier area loss of -9.78 +/- 1.52 km(2) between 1998 and 2020, with annual rate increase from -0.15 +/- 0.01 km(2) a(-1) (1998-2005) to -0.58 +/- 0.10 km(2) a(-1) (2005-2020), and an average thinning of 0.60 +/- 0.26 m a(-1) (2 sigma) between 2000 and 2014. No clear correlation was found between retreat or thinning rates and Accumulation Area Ratio (AAR), terminus slope, aspect, or glacier type. While ERA5 reanalysis data shows no significant climatic trends in temperature or precipitation, a small warming trend below our detection record is the most likely cause of the observed retreat and thinning of the Santa Ines Icefield.
Keywords: glacier inventory; recent variations; patagonia